Effect of foot health and quality of life in patients with Parkinson disease: a prospective case-control investigation - Navarro-Flores, Emmanuel María; Jiménez-Cebrián, Ana María; Becerro-de-Bengoa-Vallejo, Ricardo; Calvo-Lobo, César; Losa-Iglesias, Marta Elena; Romero-Morales, Carlos; López-López, Daniel; Palomo-López, Patricia (Elsevier, 2022)
Background Parkinson's disease (PD) is a common neurodegenerative disorder, characterised by the presence of motor disturbances. Therefore, it can be related to musculoskeletal and orthopaedic problems, particularly in the foot status, that are linked to a negative effect on overall health, mobility and social function. Objective The aim was to analyse the impact of foot health and quality of life in patients with Parkinson's disease and people without Parkinson's disease, with normalised reference scores, in the light of the values recorded with regard to foot health status and overall health. Material and methods This is a prospective case-control investigation. A sample of Parkinson's patients (n = 62) including 24 men and 38 women was recruited, and foot HQoL was measured using the Foot Health Status Questionnaire Spanish (Sp_FHSQ). Results The PD group recorded lower levels of foot health quality of life (HQoL) with lower scores on the Sp_FHSQ in general foot health, general health, physical activity, social capacity and vigour sub-scales. Regarding the rest of the sub-scales of the Sp_FHSQ, foot pain showed higher values in the PD group. Differences between the cases and control groups were analysed by means of a Mann–Whitney U test, showing statistical significance (P < 0.05). Conclusions PD presents an increased negative impact on foot health and quality of life which appears to be related to the chronic neurodegenerative disease.
Keywords: Parkinson, Enfermedad de; Sistema nervioso - Degeneración; Pies - Lesiones y heridas; Deformidades del pie; Enfermedades del pie; Dolor de pie; Calidad de vida; Medición psicosométrica